Sacred communication: Exploring the attributes of health promotion programs in the faith-based media - Ahmad, Mohd Khairie (2009)
Cultural sensitivity is a widely accepted principle among health behaviour and health communication researcher.However, studies that focus on faith-based health communication in particular on Islamic perspective or practices are rare.In contrast, the emergent and increasing of faith based media or communication institutions have significantly marked a growing interest to understand health promotion from cultural sensitivity such as Islamic communication. Thus, based on present study of 13 health promotion programs broadcasted by an Islamic radio station in Malaysia, this paper explored the attributes and practices of the faith based media in promoting health.The 390 minutes length of data was examined by employing thematic analysis using qualitative analysis software-NVivo version 8. In particular, this paper has three objectives: (i) briefly discuss the values and characteristics that formulate Islamic communication in health promotion; (ii) examine the characteristics of Islamic health promotion; and (iii) pointing out the potential and challenges of Islamic health communication in Malaysia. The insight of this paper may contribute to the understanding of Islamic communication in media and its impact for social change agenda such as on health promotion to Muslim community.These findings may also contribute to further development of health promotion strategy for Muslim communities in Islamic nation or non-Islamic nation.